Beyond Language Learning: A Critical Examination of Neoliberal Discourse in Vocational High School English Textbook - Hastowohadi, Hastowohadi; Kumaini, Ruston; Hadiwijaya, Munawwir (UIBU, 2025)
This study critically examines the presence and representation of neoliberal discourse in a Vocational High School English textbook used in Indonesia. Drawing on Critical Discourse Analysis (CDA), the research uncovers how the textbook's language, content, and imagery reflect and perpetuate neoliberal ideologies, including individualism, competitiveness, and market-driven values. The researchers collected the data from an English textbook of a vocational high school in Indonesia, representing the neoliberal aspect. By analyzing textual and visual elements, this study reveals how such ideologies subtly shape students' perceptions of success, identity, and societal roles beyond language learning objectives. The findings demonstrate that the textbook serves as a tool for language acquisition and a medium for ideological dissemination, promoting values aligned with global neoliberal norms. This research highlights the importance of critically evaluating educational materials to ensure they align with the holistic development of students and local cultural contexts. We recommend that curriculum developers, policymakers, and educators foster a more balanced and contextually relevant approach to English language education.